Renal functional reserve in patients with severe chronic obstructive pulmonary disease. Issue 5 (May 1997) - Sharkey, R A; Mulloy, E M; Kilgallen, I A; O'Neill, S J
Abstract : BACKGROUND: Renal functional reserve is the normal increase in renal blood flow after a protein load, and reduced or absent renal functional reserve is an early index of renal impairment. Renal blood flow is frequently reduced during acute oedematous exacerbations of chronic obstructive pulmonary disease (COPD). It is possible that patients with severe COPD in the stable state may have a reduced or absent renal functional reserve which could be a factor in oedema formation. METHODS: Sixteen stable patients with severe COPD and five normal controls were studied. The mean (SD) arterial oxygen and carbon dioxide tensions (PaO2, PaCO2) and forced expiratory volume in one second (FEV1) of patients with COPD were 8.1 (1.04) kPa, 6.3 (0.69) kPa, and 0.74 (0.27) 1, respectively. The pulsatility index (PI), an index of renovascular resistance, was measured non-invasively by Doppler ultrasonography at baseline and at intervals after a protein load of 250 g steak. RESULTS: The PI fell after the protein load in the normal subjects from 1.04 (0.19) to 0.84 (0.17), mean difference 0.20, 95% confidence interval of difference (CI) 0.14 to 0.27, p < 0.001. In the COPD group there was no change; baseline PI = 1.04 (0.16), PI after protein load = 1.08 (0.19), mean difference = -0.04, 95% CI-0.11 to 0.04, p = NS. Six of the patients with COPD were normocapnic and 10 were hypercapnic (PaCO2 > or = 6.0 kPa). The normocapnic patients had no significant change in PI (baseline PI = 1.07 (0.15), PI after protein load = 1.01 (0.16), mean difference = 0.06, 95% CI -0.03 to 0.15) while in the hypercapnic patients the PI tended to rise (baseline PI = 1.03 (0.17), PI after protein load = 1.12 (0.21), mean difference = -0.09, 95% CI 0.18 to 0.007, p = 0.06). CONCLUSIONS: Renal haemodynamics were unchanged after a protein load in patients with severe COPD, suggesting that they had no renal functional reserve. This may be a factor in the development of oedema frequently seen in patients with severe COPD, particularly in hypercapnic patients.